Fees Paid to Audit Firms, Accrual Choices, and Corporate Governance - Larcker, David F.; Richardson, Scott A. (Journal of Accounting Research, 2004)
We examine the relation between the fees paid to auditors for audit and non‐audit services, and the choice of accrual measures for a large sample of firms. Using our pooled sample, we find that the ratio of non‐audit fees to total fees has a positive relation with the absolute value of accruals similar to Frankel, Johnson, and Nelson [2002]. However, using latent class mixture models to identify clusters of firms with a homogenous regression structure reveals that this positive association only occurs for about 8.5% of the sample. In contrast to the fee ratio results, we find consistent evidence of a negative relation between the level of fees (both audit and non‐audit) paid to auditors and accruals (i.e., higher fees are associated with smaller accruals). The latent class analysis also indicates that this negative relation is strongest for client firms with weak governance. Overall, our results are most consistent with auditor behavior being constrained by the reputation effects associated with allowing clients to engage in unusual accrual choices.